Etimologia e pronúncia dos nomes dos Squamata do Brasil. Parte 1: Amphisbaenia - Costa, Henrique C.; Rigolon, Rafael G. (Herpetologia Brasileira, 2026)
We present here the etymology and a proposed pronunciation of the scientific names of the Brazilian Amphisbaenia. Our approach includes the valid names of 81 species, three subspecies, three genera, and one family, as well as the clades Amphisbaenia and Squamata. The class and grammatical gender of each name are also provided, and two specific names are corrected to agree with the grammatical gender of the generic name to which they are attached.